Kings and pawns : Jackie Robinson and Paul Robeson in America - Bryant, Howard, 1968- (Mariner Books, 2026)
"A path-breaking work of biography of two American giants, Jackie Robinson and Paul Robeson, whose lives would forever be altered by the Cold War, and would explosively intersect before its most notorious weapon, the House Un-American Activities Committee -- from one of the best sports and culture writers working today."--